(untitled) (Chittagong University Journal of Biological Sciences, 2024)
The present study attempted an empirical investigation to explore the stress and aggression of orphans as a function of gender and residence. A total of 120 respondents constituted the sample of the study. Among them 60 orphans were male (30 were urban and 30 were rural) and 60 orphans were female (30 were urban and 30 were rural). An adapted Bangla version (Fahim 2001) of ‘How stressful your life stress’ scale and Bangla version (Rahman 2003) of Measure of Aggressive Behavior (MAB) scale were used for data collection. Data were analyzed by mean, standard deviation, Pearson Product Moment Correlation and two-way analysis of variance (ANOVA). The findings of the present study showed that female orphans had significantly more stress (F=6.73, df=1, p<0.05) than male orphans and urban orphans had significantly more stress (F=24.36, df=l, p<0 .01) than rural orphans. No significant interaction effect was found between gender and residence according to stress. On the other hand, male orphans had significantly more aggression (F=33.46, df=l, p<O.O l) than female orphans and urban orphans had significantly more aggression (F=9.41, df=l, p<0.01) than rural orphans. No significant interaction. effect was found between gender and residence in relation to aggression. Results also showed that stress was positively correlated (r =.38, p<0.01) with aggression. The Chittagong Univ. J B. Sci. 8(1&2): 51-62, 2013